Do íntimo ao compartilhado: fotoperformance como meio de narrativa poética - Tavares, Tatiana Maria de Aguiar (2023)
Photography and performance were seen as separate categories that came together only for the act of recording, but since the 1960s both have been the stage for multiple joint experiments, with no hierarchy between the languages. Thus, the term photoperformance appears and covers a large number of works carried out that until then did not have a specific nomenclature. This research consists of a study, which through the creative process united with bibliographical research, seeks to reach an understanding of what photoperformance is. Here, five photoperformatic works will be presented, which depart from autobiographical questions, created from this understanding.